Autologous Bone Plug Supplemented With Autologous Chondrocyte Implantation in Osteochondral Defects of the Knee. (May 2016) - Bhattacharjee, Atanu; McCarthy, Helen S.; Tins, Bernhard; Roberts, Sally; Kuiper, J.H.; Harrison, Paul E.; Richardson, James B.
Background: Structural and functional outcome of bone graft with first- or second-generation autologous chondrocyte implantation (ACI) in treating cartilage and subchondral bone defect has not been reported previously. Purpose: To evaluate the outcome of simultaneous transplantation of an autologous bone plug with first- or second-generation ACI for restoration of concomitant subchondral bone and full-thickness cartilage defect in the femoral condyle of the knee. Study Design: Case series; Level of evidence, 4. Methods: Seventeen patients (mean ± SD age, 27 ± 7 years; range, 17-40 years)—12 with osteochondritis dissecans (International Cartilage Repair Society [ICRS] grades 3 and 4) and 5 with an isolated osteochondral defect (ICRS grade 4)—had the defect reconstructed with implantation of a unicortical autologous bone graft combined with ACI (the OsPlug technique). Functional outcome was assessed with Lysholm scores obtained preoperatively and at 1 and 5 years postoperatively. The repair site was evaluated with the Oswestry Arthroscopy Score (OAS), MOCART score (magnetic resonance observation of cartilage repair tissue), and ICRS II histology score. Formation of a subchondral lamina and lateral integration of the bone grafts were evaluated from magnetic resonance imaging scans. Results: The mean defect size was 4.5 ± 2.6 cm 2 (range, 1-9 cm 2 ), and the mean depth was 11.3 ± 5 mm (range, 5-18 mm). The preoperative Lysholm score improved from 45 (interquartile range [IQR], 24; range, 16-79) to 77 (IQR, 28; range, 41-100) at 1 year ( P = .001) and 70 (IQR, 35; range, 33-91) at 5 years ( P = .009). The mean OAS of the repair site was 6.2 (range, 0-9) at a mean of 1.3 years. The mean MOCART score was 61 ± 22 (range, 20-85) at 2.6 ± 1.8 years. Histology demonstrated generally good integration of the repair cartilage with the underlying bone. Poor lateral integration of the bone graft, as assessed on magnetic resonance imaging scan, and a low OAS were significantly associated with a poor Lysholm score and failure. A total of 3 patients had treatment failure, with 1 requiring total knee replacement at 5 years (Lysholm score of 33 at failure) and the other 2 requiring further surgical intervention because of persistent symptoms at 2 and 4 years, respectively (both had Lysholm score of 45 at failure). The Lysholm score in these patients before failure were still noted to be higher than at the preoperative level. Conclusion: The OsPlug technique shows significant improvement of functional outcome for up to 5 years in patients with high-grade osteochondritis dissecans or osteochondral defect. This is the first report describing association of bone graft integration with functional outcome after such a procedure. It also demonstrates histologic evidence of integration of the repair cartilage with the underlying bone graft.